Small bowel obstruction due to congenital omphalomesenteric band with concomitant appendicitis in the third trimester of pregnancy: A case report - Krishnamurthy, Aparna; Jena, Salil; Goel, Vishal; Grewal, Roobina (Indian Journal of Case Reports, 2026)
Acute abdomen during pregnancy remains a diagnostic challenge due to altered anatomy and physiological changes. Appendicitis is the most common non-obstetric surgical emergency in pregnancy, whereas small bowel obstruction is rare and usually attributed to post-operative adhesions. Congenital causes such as persistent omphalomesenteric duct remnants are exceptionally uncommon in adults and rarely reported during pregnancy. We report a 34-yearold primigravida at 30 weeks and 4 days’ gestation presenting with progressive abdominal pain and leukocytosis. Ultrasonography demonstrated localized ileus with ascites. Emergency laparotomy revealed closed-loop obstruction due to a fibrous omphalomesenteric band with 75 cm of gangrenous distal ileum and concomitant acute appendicitis. Segmental resection with primary anastomosis and appendectomy were performed. Intraoperative fetal bradycardia necessitated emergency cesarean delivery. Both mother and neonate recovered satisfactorily. The case highlights the need for early surgical intervention and multidisciplinary coordination in managing an acute abdomen during pregnancy.